2020
DOI: 10.1002/brb3.1537
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms and motor levodopa‐induced complications in Parkinson's disease

Abstract: Objective The aim of the study was to evaluate the association of individual and combined single‐nucleotide polymorphisms in brain‐derived neurotrophic factor (BDNF), dopamine transporter (DAT), and catechol‐O‐methyltransferase (COMT) genes with the occurrence of motor levodopa‐induced complications (MLIC) in Parkinson's disease (PD). Materials and Methods We studied 76 patients with PD (MLIC occurred in 56.6%) and 60 controls. Allelic discrimination of rs6265 BDNF (Val66Met), rs397595 DAT (SLC6A3), and rs4680… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…An increasing number of studies have focused on the relationship between the risk of PD and BDNF SNPs, especially rs6265, although strong evidence is yet to be presented ( 28 ). Michałowska et al ( 29 ) identified that the variation of rs6265 increased the risk of PD. However, Pal et al ( 28 ) and Svetel et al ( 30 ) found that the allele frequency and genotype distribution in patients with PD and healthy controls did not deviate significantly.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have focused on the relationship between the risk of PD and BDNF SNPs, especially rs6265, although strong evidence is yet to be presented ( 28 ). Michałowska et al ( 29 ) identified that the variation of rs6265 increased the risk of PD. However, Pal et al ( 28 ) and Svetel et al ( 30 ) found that the allele frequency and genotype distribution in patients with PD and healthy controls did not deviate significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the PD-related susceptibility genes have been also associated with levodopa-induced motor complications in PD patients; for instance, polymorphisms in MAO-B and COMT genes have been shown to increase the risk of developing dyskinesias and wearing-off [ 143 ]. Furthermore, specific BDNF, DAT , and COMT variants have been demonstrated to exert a synergistic effect on levodopa-induced motor complications [ 144 ]. Coffee consumption has been associated with a reduced risk of levodopa-induced dyskinesias in PD patients [ 145 ].…”
Section: Potential Implications For Diagnosis and Therapymentioning
confidence: 99%
“…A few studies have been conducted on the variants encoding enzymes associated with dopamine metabolism pathway [61,62,75,83]. Lack of dopamine in synapses is a main clinical indication of PD.…”
Section: Other Genetic Analysis In Polandmentioning
confidence: 99%
“…They found that rs6265 BDNF (p.Val66Met) was associated with risk of PD. Additionally, they observed a synergic effect of rs6265 BDNF (p.Val66Met), rs397595 DAT (SLC6A3), and rs4680 COMT (p.Val158Met) polymorphisms on the occurrence of motor levodopa-induced adverse effects [83]. In a study of 158 patients with PD and 139 controls, Tan et al [77] analysed seven SNPs from MDR1 responsible for regulating environmental xenobiotics, but found no significant differences between the two groups.…”
Section: Other Genetic Analysis In Polandmentioning
confidence: 99%